Pharmacokinetics of cannabidiol following single oral and oral transmucosal administration in dogs - della Rocca, Giorgia; Paoletti, Fabiola; Conti, Maria Beatrice; Galarini, Roberta; Chiaradia, Elisabetta; Sforna, Monica; Dall'Aglio, Cecilia; Polisca, Angela; Di Salvo, Alessandra (Frontiers in Veterinary Science, 2023)
In the last few years, different formulations containing cannabidiol (CBD) were tested with regard to its efficacy on chronic pain, refractory epilepsy, anxiety, aggressive behavior and atopic dermatitis in dogs. CBD is generally administered orally, but its low bioavailability, probably due to a first-pass metabolism, represents a great limitation. The aim of this study was to evaluate if CBD bioavailability increases after oral transmucosal administration (OTM) compared to oral treatment. Twelve dogs diagnosed with mild chronic pain were enrolled in the study and treated once orally or OTM (6 dogs/group) with a pure CBD in oil formulation at a dosing rate of 1 mg/kg b.w.. At prefixed time points, blood samples were collected to define CBD plasma concentrations vs time profiles, and the main pharmacokinetics parameters were obtained by non-compartmental model. CBD Cmax, Tmax, terminal half-life and AUC0-t were 206.77 ± 167 and 200.33 ± 158.33 ng/mL, 2.17 ± 0.98 and 1.92 ± 1.11 hours, 2.67 ± 0.53 and 2.62 ± 0.64 hours, 647.51 ± 453.17, and 536.05 ± 370.21 h* ng/mL, following oral and OTM administration, respectively. No significant difference in pharmacokinetic parameters were observed between treatments. The OTM administration did not increase cannabidiol bioavailability compared to oral treatment. The almost perfectly superimposable mean plasma concentrations of cannabidiol following the two treatments suggests that CBD is not able to be adsorbed by the oral mucosa or that its absorption is very scarce, and that CBD is swallowed and absorbed in the gastrointestinal tract